Divergent nanostructures from identical ingredients: unique amphiphilic micelle template for polyaniline nanofibers, tubes, rods, and spheres - Anilkumar, P.; Jayakannan, M. (Macromolecules, 2008)
Here, we report a unique soft templating approach based oil all in-built amphiphilic azobenze-nesulfonic acid for tuning various types of polyaniline nanomaterials Such as fibers, rods, spheres, and tubes. The dopant molecule is freely soluble in water, and DLS measurements Of the resultant Solution revealed that it forms spherical micelles of diameter similar to 4.29 nm. The addition of aniline induces self-organization in the dopant micelles which produce micrometer-sized cylindrical aggregates or layerlike assemblies depending upon the aniline/dopant composition in the feed. In the emulsion route. the oxidation of these cylindrical or layerlike micelle aggregates produce nanofibers and nanotubes, respectively. The dilution of thick emulsion microaggregates led to the formation Of uniformly distributed small 175 nm aggregated micelles. which template for the nanorods (dilution route). Alternatively, the dopant micelles form spherical shape aggregates with oxidizing agent ammonium persulfate (APS) in water. Aniline molecules diffuse through the organic/aqueous interface and get absorbed at these spherical aggregates, and subsequent chemical oxidation produces exclusively polyaniline nanospheres (interfacial route). The mechanism of the polyaniline nanomaterials formation was investigated by dynamic light scattering (DLS) and high-resolution transmission electron microscopy (TEM). DLS studies of the polymerization mixtures in water evident for the formation of micrometer range aggregates. TEM analysis confirmed the shape of the template as cylindrical, cylindrical + spherical, and spherical geometry for the complexes of dopant with aniline and APS in the emulsion, dilution, and interfacial routes, respectively. The amphiphilic nature of the dopant solubilizes the nanomaterials in water and organic solvents, and the optical properties of nanomaterials were studied in various solvents by UV-vis spectroscopy. The wide-angle X-ray diffraction Studies confirmed the appearance of a new peak at lower angle (d = 13.6 angstrom) corresponding to the highly crystalline and ordered polyaniline nanomaterials. The solid-state properties of the nanomaterials were found to he highly dependent on the size and shape of polymerization templates employed for the synthesis.

Hydroxyl-functionalized polyaniline nanospheres: tracing molecular interactions at the nanosurface via vitamin C sensing - Anilkumar, P.; Jayakannan, M. (Langmuir, 2008)
Here, we report a synthesis of novel polyaniline nanospheres bearing mono- and bishydroxyl functional groups were to trace the molecular interactions at the nanosurfaces through vitamin C sensing. Two new aniline monomers synthesized via a tailor-made approach and polymerized to produce soluble and uniform polyaniline nanospheres. The structures of the monomers and polymers were characterized by NMR, FT-IR, and MS techniques, and the morphology of the nanomaterials was analyzed by SEM and TEM. The mechanistic aspects of the nanomaterial formations were analyzed by FT-IR and dynamic light scattering techniques. These studies revealed that the hydroxyl-functionalized monomers have strong hydrogen bonding at the monomer level and form spherical aggregates in water, which are templates for the polyaniline nanospheres 600 +/- 100 nm in size. A controlled synthesis was also carried out using aniline hydrochloride as an unsubstituted counterpart, which yields polyaniline nanofibers. WXRD analysis confirmed the presence of a sharp peak at lower angle at 2 theta = 7.3 degrees (d-spacing of 13.4 angstrom) in hydroxyl-substituted nanospheres with respect to enhancement of solid-state ordered crystalline domains, whereas unsubstituted nanofibers were found to be highly amorphous. Vitamin C was employed as an analyte to trace the molecular interaction at the nanosphere surface and Study the influence of nanosurface functionalization on the sensing ability of biomolecules. The bishydroxyl-functionalized polyaniline nanospheres were found to show efficient molecular interactions toward vitamin C, whereas nanospheres with a monohydroxyl group or unsubstituted nanofibers failed as sensing materials. In a nut shell, in the present investigation, for the first time, we have proved the importance of surface functionalization of polyaniline nanomaterial, exclusively nanospheres, using hydroxyl groups for studying the molecular interactions at the nanosurfaces with biomolecules such as vitamin C.

Solvent-free and nonisocyanate melt transurethane reaction for aliphatic polyurethanes and mechanistic aspects - Deepa, P.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
A novel melt transurethane polycondensation route for polyurethanes under solvent-free and nonisocyanate condition was developed for soluble and thermally stable aliphatic or aromatic polyurethanes. The new transurethane process was investigated for A + 13, A-A + B, and A-A + B-B (A-urethane and B-hydroxyl) type condensation reactions, and also monomers bearing primary and secondary urethane or hydroxyl functionalities. The transurethane process was confirmed by H-1 and C-13 NMR, and molecular weight of the polymers were obtained as M-n = 10-15 X 10(3) and M-w = 15-45 X 10(3) g/mol. The mechanistic aspects of the melt transurethane process and role of the catalyst were investigated using model reactions, H-1 NMR, and MALDI-TOF-MS. The model reactions indicated the occurrence of 97% reaction in the presence of catalyst, whereas its absence gave only less than 2% of the product. The polymer samples were subjected for end-group analysis using MALDI-TOF-MS, which confirms the Ti-catalyst mediated nonisocyanate pathway in the melt transurethane process. Almost all the polyurethanes were stable up to 280 degrees C, and the T-g of the polyurethanes can be easily fine-tuned from -30 to 120 degrees C by using appropriate diols in the melt transurethane process. (C) 2008 Wiley Periodicals, Inc.
Keywords: MALDI; melt polymerization; nonisocyanate; Polycondensation; polyurethanes; thermal stability; transurethane

Carboxylic-functionalized water soluble pi-conjugated polymer: highly selective and efficient chemosensor for mercury(II) ions - Balamurugan, A.; Reddy, M. L. P.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Here, we report a new carboxylic-functionalized water soluble pi-conjugated polymer for selective detection of highly toxic Hg(2+) in neutral pH condition. carboxylic-functionalized thiophene containing oligophenylenevinylene was synthesized and polymerized under oxidative route to obtain water soluble polymer. Free carboxylic groups present in the pi-conjugated materials provide opportunity to use pH as external stimuli for studying secondary interaction such as hydrogen bonding and aromatic pi-stacking of the chromophores. The pH changes strongly influence on the molecular interactions in the monomer, whereas the long chain polymer was less disturbed. The polymer showed high selectivity for detecting Hg(2+) ions compared with any other transition metal ions in water. The detection efficiency of the polymer was found almost 40 times higher than that of its monomeric unit. Stern-Volmer constant for the Hg(2+) ion sensing was determined through concentration dependent studies as 6.4 x 10(5) M(-1). The carboxylic-functionalized polymer showed reversibility in the metal-ion detecting capabilities which was further investigated by NaCl complexation with Hg(2+) complex. Both funneling of excitation energy to the Hg(2+) center and also excitation energy migration through chain pi-conjugated backbone were correlated to the superior sensing characteristics of the polymer compared to its monomeric counterpart. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 5144-5157, 2009
Keywords: conjugated polymer; pH sensitive; photophysical studies; sensing; synthesis; water soluble

Control of molecular aggregation in symmetrically substituted pi-conjugated bulky poly(p-phenylenevinylene)s and their copolymers - Resmi, R.; Amrutha, S. R.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A new series of symmetrically substituted bulky PPV-copolymers based on poly(bis-2,5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (BEH-PPV) bearing tricyclodecane (TCD) pendants were synthesized to study the effect of chain aggregation in the pi-conjugated polymer backbone. The composition of the copolymers was varied up to 100 mol % and the structures of the copolymer were confirmed by NMR and FTIR. The molecular weights of the copolymers were obtained as M(w) = 11,500-1,78,800 depending on the TCD-incorporation in BEH-PPV. The origin of the pi-aggregation was investigated using mixture of solvents (polar or nonpolar) or temperature as external stimuli. Absorption, photoluminescence, and time-resolved fluorescence decay techniques were employed as tools to trace molecular aggregation in solution and solid state. The TCD-substituted bulky copolymers showed almost twice the enhancement in photoluminescence compared with that of BEH-PPV Solvent-induced aggregation studies of copolymers revealed the existence of strong molecular aggregation in BEH-PPV compared with that of bulky copolymers. Variable temperature studies further evidence for the reversibility of molecular aggregation on beating/cooling cycles and showed isosbetic points with respect to free and aggregated polymer chains. Time-resolved fluorescent studies confirmed the existence of free and aggregated pi-conjugated species with a life time of 0.1 to 1.0 ns. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2631-2646, 2009
Keywords: conjugated polymers; fluorescence; poly(p-phenylenevinylene); solution properties; Structure-property relationship

Self-assembled cylindrical and vesicular molecular templates for polyaniline nanofibers and nanotapes - Anilkumar, P.; Jayakannan, M. (Journal of Physical Chemistry B, 2009)
We report a soft template approach based on a custom-designed novel surfactant-cum-dopant for size and shape tuning of polyaniline nanomaterials such as nanofibers and nanotapes via emulsion and dispersion polymerization routes. A new amphiphilic 4-(3-dodecyl-8-enylphenyloxy) butane sulfonic acid was synthesized by ring-opening of butanesultone with renewable resource cardanol. The new amphiphilic dopant forms spherical micelles in water and its critical micelle concentration was determined by dye encapsulation and surface tension methods. In the emulsion route, the amphiphilic dopant complexed with aniline to produce cylindrical micellar aggregates that template exclusively for polyaniline nanofibers. The dispersion of aniline + dopant in water/toluene solvent mixture produces vesicles that selectively template for polyaniline nanotapes. The mechanism of the polyaniline nanomaterials formation was investigated by dynamic light scattering (DLS) and high-resolution transmission electron microscopy (HR-TEM). DLS of the polymerization templates in water proved the presence of micrometer range aggregates, and TEM images confirmed the shape of the cylindrical and vesicular templates. The polyaniline nanomaterials were found soluble in water and polar organic solvents for structural characterization and composition analysis by H-1 NMR spectroscopy. Absorbance spectra of the nanomaterials showed free carrier tail above 900 nm in the near IR region for the delocalization of electrons in the polaron band Corresponding to expanded conformation of polyaniline chains, Wide angle X-ray diffraction showed two new peaks at low angle region with d-spacing of 26.5 and 13.6 angstrom Corresponding to lamellar ordering of polyaniline chains followed by interdigitations of the amphiphilic dopant in the nanomaterials.

Supramolecular ring banded prototype liquid crystalline oligo(phenylenevinylene) - Amrutha, S. R.; Jayakannan, M. (Journal of Physical Chemistry B, 2009)
We report a new ring banded supramolecular structure in thermotropic liquid crystalline oligo(phenylenevinylene) (OPV) via a melt crystallization process. A series of structurally different OPV molecules were synthesized using tricyclodecanemethanol (TCD) as a bulky pendant unit to trace ring banded morphology. Among all, an OPV molecule with rigid bis-TCD units in the central core and flexible dodecyl chains at the outer phenyl rings (BTCD-BDD-OPV) was found to show ring banded morphologies, which is a first of its kind in T-conjugated materials. BTCD-BDD-OPV experiences strong aromatic pi-pi interactions in both film and liquid crystalline (LC) frozen stage. The pi-induced aggregation leads to lamellar self-assembly of OPV-mesogens that subsequently undergo helical crystal growth, thereby producing dark and bright ring banded patterns. Variable temperature X-ray diffraction analysis revealed the existence of three peaks at 27.07, 13.97, and 8.90 angstrom corresponding to 001, 002, and 003 fundamental layers, respectively, thus confirming the lamellar self-assembly of OPV-mesogens. Electron microscopic (SEM and TEM) analysis of the LC frozen sample showed images confirming helical microcrystalline assembly and providing direct evidence for the self-organization mechanism. Detailed photophysical experiments such as excitation, emission, and timeresolved fluorescence decay studies indicated that BTCD-BDD-OPV has very strong pi-pi interaction in both film and LC frozen stage, which was found to be main driving force for the formation of supra-ring structure. Upon illumination with light, the OPV chromophores in the LC phase were excited and the color of the samples turned into luminescent green ring bands.

Novel supramolecular organogel nanotubular template approach for conducting nanomaterials - Anilkumar, P.; Jayakannan, M. (Journal of Physical Chemistry B, 2010)
We report a unique supramolecular organogel template approach for conducting polyaniline nanomaterials. A novel organogel based on sulfonic acid dopant was designed and developed from renewable resource 3-pentadecyl phenol via ring-opening of 1,4-butane sultone. The amphiphilic dopant molecule formed thermo-reversible supramolecular organogel in highly polar solvents like alcohols. The self-assembled fibril network morphology of the gel was confirmed by scanning electron microscopy (SEM) and atomic force microscopy. Transmission electron microscopy (TEM) revealed that the inner part of the fibrous gel is nanotubular with the pore diameter of similar to 75 run. The organogel nanotubular morphology was retained even in the presence of aniline+dopant complex, and the aniline monomers occupied the hydrophobic nanopockets provided by the amphiphilic dopant. The chemical oxidative polymerization of the dopant+aniline organogel template produced well-defined polyaniline nanofibers. The polymerization was carried out at various temperatures to establish the role of the physical state and stability of the organogel on the morphology. The sulfonic acid molecule acts both as self-assembled molecular template for the synthesis of polymer nanomaterial as well as anionic counterpart for stabilizing the positively charged conducting polymer chains. The gel template played a pivotal role in directing polyaniline chains to form nanofibers and also manipulating the number of other properties such as conductivity, solubility, percent crystallinity, and solid-state ordering, etc. Temperature-dependent electrical conductivity measurements revealed that the nanomaterials showed typical linear ohmic behavior and also followed the 3-D VRH model at elevated temperatures.